Penerapan Teknik Relaksasi Benson Sebagai Upaya Mengurangi Nyeri Akut Pasien Pasca Operasi Benigna Prostatic Hyperplasia (BPH) - Septi Viantri Kurdaningsih; Rahayu Tri Nuritasari; Neng Annis Fathia; Sunarmi Sunarmi (Jurnal Keperawatan Muhammadiyah, 2023)
Objective: The purpose of this study was to determine Benson relaxation can reduce the intensity of acute pain on patients post Benign Prostatic Hyperplasia (BPH) surgeryMethods:   The design used was descriptive analytics with a case study approach. The research subjects were two patients post Benign Prostatic Hyperplasia (BPH) surgery with the following inclusive criteria: man, age between 40 and 60, can communicate well, has good hearing, and willing to sign an informed consent. This research was carried out at Ibnu Rusyd room, Muhammadiyah Hospital, Palembang, on 20-26 April 2022. The data collecting was done through observation and interview. The data analysis was done by comparing the theories and data found on the patients.Results:   The results of the research were obtained from the two respondents with pain complaints; before the treatment of Benson relaxation, the pain was medium (4-6), and after Benson relaxation, the pain was light (1-3). Benson relaxation has been proven to be able to reduce the intensity of acute pain on patients post Benign Prostatic Hyperplasia (BPH) surgery.Conclusion:  Benson relaxation recommended to be implemented as a treatment of acute pain problems on patients post Benign Prostatic Hyperplasia (BPH) surgery